World mark encyclopedia of cultures and daily life - Gall, Timothy L. (Detroit : GALE, 1998)
Provides information on 500 cultures of the world, covering twenty different areas of daily life including clothing, food, language, and religion
Vol 4
Includes bibliographical references and indexes.
Keywords: Ethnology -- Encyclopedias, Juvenile; Manners and customs -- Encyclopedias, Juvenile; Ethnology -- Encyclopedias; Manners and customs -- Encyclopedias